Oral administration of live combined Bacillus subtilis and Enterococcus faecium alleviates colonic oxidative stress and inflammation in osteoarthritic rats by improving fecal microbiome metabolism and enhancing the colonic barrier - Tang, Jilang; Song, Xiaopeng; Zhao, Mingchao; Chen, Hong; Wang, Yingying; Zhao, Binger; Yu, Shiming; Ma, Tianwen; Gao, Li (Frontiers in Microbiology, 2022)
Osteoarthritis (OA) causes intestinal damage. The protective effect of probiotics on the intestine is indeed effective; however, the mechanism of protection against intestinal damage in OA is not clear. In this study, we used meniscal/ligamentous injury (MLI) to mimic OA in rats and explored the colonic protective effects of Bacillus subtilis and Enterococcus faecium on OA. Our study showed that treatment with B. subtilis and E. faecium attenuated colonic injury and reduced inflammatory and oxidative stress factors in the serum of osteoarthritic rats. α- and ß diversity of the fecal flora were not different among groups; no significant differences were observed in the abundances of taxa at the phylum and genus levels. We observed the presence of the depression-related genera Alistipes and Paraprevotella. Analysis of fecal untargeted metabolism revealed that histamine level was significantly reduced in the colon of OA rats, affecting intestinal function. Compared to that in the control group, the enriched metabolic pathways in the OA group were primarily for energy metabolisms, such as pantothenate and CoA biosynthesis, and beta-alanine metabolism. The treatment group had enriched linoleic acid metabolism, fatty acid biosynthesis, and primary bile acid biosynthesis, which were different from those in the control group. The differences in the metabolic pathways between the treatment and OA groups were more evident, primarily in symptom-related metabolic pathways such as Huntington's disease, spinocerebellar ataxia, energy-related central carbon metabolism in cancer, pantothenate and CoA biosynthesis metabolic pathways, as well as some neurotransmission and amino acid transport, and uptake- and synthesis-related metabolic pathways. On further investigation, we found that B. subtilis and E. faecium treatment enhanced the colonic barrier of OA rats, with elevated expressions of tight junction proteins occludin and Zonula occludens 1 and MUC2 mRNA. Intestinal permeability was reduced, and serum LPS levels were downregulated in the treatment group. B. subtilis and E. faecium also regulated the oxidative stress pathway Keap1/Nrf2, promoted the expression of the downstream protective proteins HO-1 and Gpx4, and reduced intestinal apoptosis. Hence, B. subtilis and E. faecium alleviate colonic oxidative stress and inflammation in OA rats by improving fecal metabolism and enhancing the colonic barrier.